Reprogrammed mRNA translation drives resistance to therapeutic targeting of ribosome biogenesis. (18th September 2020) - Kusnadi, Eric P; Trigos, Anna S; Cullinane, Carleen; Goode, David L; Larsson, Ola; Devlin, Jennifer R; Chan, Keefe T; De Souza, David P; McConville, Malcolm J; McArthur, Grant A; Thomas, George; Sanij, Elaine; et al.
Abstract: Elevated ribosome biogenesis in oncogene‐driven cancers is commonly targeted by DNA‐damaging cytotoxic drugs. Our previous first‐in‐human trial of CX‐5461, a novel, less genotoxic agent that specifically inhibits ribosome biogenesis via suppression of RNA polymerase I (Pol I) transcription, revealed single‐agent efficacy in refractory blood cancers. Despite this clinical response, patients were not cured. In parallel, we demonstrated a marked improvement in the in vivo efficacy of CX‐5461 in combination with PI3K/AKT/mTORC1 pathway inhibitors. Here, we reveal the molecular basis for this improved efficacy observed in vivo, which is associated with specific suppression of translation of mRNAs encoding regulators of cellular metabolism. Importantly, acquired resistance to this cotreatment is driven by translational rewiring that results in dysregulated cellular metabolism and induction of a cAMP‐dependent pathway critical for the survival of blood cancers including lymphoma and acute myeloid leukemia. Our studies thus identify key molecular mechanisms underpinning the response of blood cancers to selective inhibition of ribosome biogenesis and define metabolic vulnerabilities that will facilitate the rational design of more effective regimens for Pol I‐directed therapies. Synopsis: Specific inhibition of rRNA synthesis has been reported as an effective new treatment for refractory blood cancer, but patients relapse. Here, the development of resistance is shown to depend on reprogrammed mRNA translation and subsequent upregulation of a metabolism‐dependent survival pathway. The efficacy of acute, combinatorial ribosome‐targeting therapy in vivo is associated with downregulation of the cells' translational activity and energy metabolism Therapeutic resistance is mediated by translational alterations that promote elevated metabolic activity and activate a cAMP‐dependent pro‐survival mechanism The induced pro‐survival mechanism acts via EPAC1/2 and is targetable by metformin in vitro and in vivo The identified metabolic vulnerability of ribosome‐targeting therapy resistance can be exploited to improve treatment efficacy in hematological cancers including lymphoma and acute myeloid leukemia. Abstract : The elevated metabolic activity and activation of cAMP‐dependent pro‐survival mechanisms that lead to resistance of hematological cancers towards rRNA synthesis inhibition also poses a potentially targetable vulnerability.